Analysis of Employee Work Motivation In The Scope of Tanralili Sub-district Gov-ernment, Maros Regency - Asrin Tandi (Green Publisher Indonesia, 2024)
This research aims to analyze employee work motivation, focusing on physiological, safety, social, esteem, and self-actualization needs within Tanralili Subdistrict Government, Maros Regency. The study utilizes a qualitative descriptive analysis approach, collecting data from primary and secondary sources through observation, informant interviews, and documentation. Data analysis involves qualitative descriptive analysis, comprising data collection, reduction, presentation, and conclusion drawing. Findings reveal that employee motivation stems from their work activities in providing administrative services. Motivation efforts aim to enhance performance, with Maslow's hierarchy of needs theory guiding motivation strategies, including: a) Addressing physiological needs through break time provision, position-based allowances, and incentives. b) Implementing safety needs via standard facilities, tools, and health benefits. c) Fulfilling social needs through community service, fostering employee relationships, and promoting positive community interactions. d) Realizing esteem needs through attention, recognition, and timely appreciation. e) Achieving self-actualization needs through study leaves, skill enhancement, and technology mastery opportunities. These strategies contribute to improved employee performance, emphasizing the importance of motivation in organizational effectiveness